Latitudinal variation of genecological traits in native grasses of Patagonian rangelands - Leva, Paula Edit (2013)
Geographical variation in genetically based traits helps to elucidate the effect of distinct ecological and evolutionary processes on widespread plants. Whereas abundant information exists on genetic patterns of woody species in western humid Andes, such information is scarce for the neighbouring dry Patagonian steppe. We examined genecological traits of two native forage species vulnerable to overgrazing (Bromus pictus and Poa ligularis) in dry Occidental Phytogeographical District. We compared within-population genetic diversity and among-population (n = 6) divergence by using isozyme electrophoresis. We also cultivated plants under common garden to compare genetically based morphology (plant height, number of tillers by plant and weight per tiller). Analysis showed that 8 and 13 loci were polymorphic of 9 and 19 resolved loci in at least one population for Bromus and Poa, respectively. In general, plant traits decreased from north to south in both species. Genetic and quantitative results (FST/QST index) showed evidence of local adaptation in populations of both species. Genetic divergence among populations was significant. We detected two different geographical groups divided at the same latitude (42–43°S) in both species, supporting the hypothesis of a past vicariance event. Sustainable management of these forage species to cope with land-use and climate change will be enriched by the inclusion of genecological knowledge.